2021
DOI: 10.3390/healthcare9060616
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor—An Innovative Indicator for Free Flap Ischemia after Microsurgical Reconstruction

Abstract: (1) Background: Nowadays, the use of microsurgical free flaps is a standard operative procedure in reconstructive surgery. Still, thrombosis of the microanastomosis is one of the most fatal postoperative complications. Clinical evaluation, different technical devices and laboratory markers are used to monitor critical flap perfusion. Macrophage migration inhibitory factor (MIF), a structurally unique cytokine with chemokine-like characteristics, could play a role in predicting vascular problems and the failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Newer techniques such as Thermal scan and Macrophage Migration Inhibitory Factor are still under evaluation but are likewise expensive. 16 An ideal flap monitoring technique should be atraumatic, inexpensive; it should produce rapid, reliable, and objective results; it should be simple to interpret even by relatively inexperienced personnel; and it should be applicable to all types of flaps. 17 The flap blood glucose method is simple and can be performed by residents, nurses, and even patients themselves, even on intraoral flaps, which are almost impossible to monitor on the basis of flap colour or temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer techniques such as Thermal scan and Macrophage Migration Inhibitory Factor are still under evaluation but are likewise expensive. 16 An ideal flap monitoring technique should be atraumatic, inexpensive; it should produce rapid, reliable, and objective results; it should be simple to interpret even by relatively inexperienced personnel; and it should be applicable to all types of flaps. 17 The flap blood glucose method is simple and can be performed by residents, nurses, and even patients themselves, even on intraoral flaps, which are almost impossible to monitor on the basis of flap colour or temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Newer techniques such as Thermal scan and Macrophage Migration Inhibitory Factor are still under evaluation but are likewise expensive. 16…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among EV subtypes, ABs inherit the characteristics of blast cells to the greatest extent. [ 9 , 24 , 41 ] Considering the versatility of stem cells, whether ABs produced by stem cells promote tissue repair to a greater extent than FSCT cell‐derived ABs, such as those produced from adipose stem cells or bone marrow MSCs, remains to be determined. We demonstrated that FSCT cell‐derived ABs inhibited KEAP1 by delivering miR‐339‐5p.…”
Section: Discussionmentioning
confidence: 99%
“…The MIF cytokine family exerts a special role in infectious diseases and inflammations (see Table 1). Aside from its role in infectious diseases, MIF plays a role in inflammatory diseases such as asthma or atherosclerosis, various forms of cancer, several autoimmune diseases, burn injuries, wound healing, and even free-flap ischemia [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. The diverse functions of the MIF protein in the immune response of the organism to microbial pathogens have been demonstrated in various studies [37,39,41,58,59].…”
Section: Sepsis Is a Life-threatening Complication Of An Infection Th...mentioning
confidence: 99%